STUDIES OF PHYSICO-CHEMICAL METHODS OF ANALYSIS IN THE PRODUCTION OF ADHESIVE MATERIALS - D. T. Kodirova (American Journals Publishing, 2023)
In the article, the physicochemical methods of analysis for the production of adhesive materials are studied.
Keywords: formaldehyde resin, adhesive compositions, high molecular weight substances.